3y-11=5-y

Simple and best practice solution for 3y-11=5-y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y-11=5-y equation:



3y-11=5-y
We move all terms to the left:
3y-11-(5-y)=0
We add all the numbers together, and all the variables
3y-(-1y+5)-11=0
We get rid of parentheses
3y+1y-5-11=0
We add all the numbers together, and all the variables
4y-16=0
We move all terms containing y to the left, all other terms to the right
4y=16
y=16/4
y=4

See similar equations:

| 6(3x-50-7x=25 | | 4x/9=8x-16 | | 90=12y-30 | | 9.25x+9=15.5x+14 | | -135=-51(-3+5x | | 3y-11=5y-y | | 7y+3=6(y+2) | | -23,5j-89,6=j+238,7 | | x8=7 | | 12=3x-42 | | 2t+21=4.5 | | 10+7n=5(-4n) | | 4/5(p-10)=8 | | 24(l)=2(1)+2(1/4) | | 3(x-9)=3(x+7) | | 8t+3t+-3t-16t=16 | | y/16=-21 | | 4x+8=-1+x+6x | | 11t-8t-t+1=13 | | 2(5x+4)=4(5x-6)-3x | | 11t–8t–t+1=13 | | x+(x+3)=27.5 | | -16p+p=15 | | 3(2m=4)=6(2+m | | 10-5(3-d)=25 | | 12(5x+4)=3(5x-5)-6x | | -2x^2+4x+7=0 | | 9(2-4m)=2(m+2) | | -10y+-20y+9y+6y–(-)19=4 | | 16=25/6x | | -10y+-20y+9y+6y–(-19)=4 | | 5.41x+5.41=10.82 |

Equations solver categories